Fatores de risco associados ao câncer do colo do útero: um estudo com usuárias da Unidade Municipal de Saúde do bairro do Guamá, Belém-Pará, 2013 - LOPES, Samantha Lira (2019)
The incidence and mortality from cervical cancer are worrying in the world, Brazil, especially in the North, which has been identified as the Brazilian region worst incident of this neoplasm. The objective of this study is to analyze the risk factors of cervical frequently the uterus in women who perform preventive screening program for Cancer Prevention Cervical cancer. The methodology applied was based on descriptive cross-sectional study. The population was 100 women, selected by random sample, using the interview technique from a form with the variables related to socioeconomic profile, and lifestyle habits of life, information about first sexual intercourse, parity, multiple partners, use hormonal contraception and STDs, with emphasis on HPV infections. To better understand the results obtained in the study, the data were organized into four parts, which are the socioeconomic profile, habits and lifestyles, ways of life and sexual parity and sexual behavior. The research was conducted at the Health Unit Guamá, a public institution in the city of Belém / PA, develops the program for prevention of Cervical Cancer and Pap test has as the main strategy for tracking and control of this malignancy. The data found in this group of women allowed to detect the risk factors most predisposing to foster the development of cervical carcinoma, checked in several literatures, including the most predominant are associated with aspects of sexual life and behavior, such as early first sexual intercourse, multiplicity of partners the presence of STDs and genital HPV infections in addition , non-use of condoms favors an increased risk of these women for cervical cancer .